STUDY ON HAROLD PINTER’S ABSURDITY - ANWAR ALAM (International Journal of Multidisciplinary Research and Studies, 2021)
Harold Pinter is widely regarded as one of the most skilled dramatists to work within the context of the Theatre of the Absurd. He was born on October 10th, 1930 in the neighborhood of Hackney, which is located in the greater London area of England. He was a great manipulator of language, which he saw not as a bridge that brings people together but as a barrier that has kept them apart. He believed that language was a barrier that kept people apart. He plays with words, and he plays on our nerves, and in this way, he has us in the palm of his hand. He is not concerned with ideas and concepts in the broadest meaning of the term. He is a dramatist who has had a significant impact on the current English theatre. Between the years of 1941 and 1947, Pinter was a student at the Hackney Downs Grammar School. It was around this time that he began composing both poetry and prose. In the school plays of Shakespeare that he participated in, he played both Macbeth and Romeo. He also developed an interest in the theatre. Pinter, who is known for being an absurdist playwright, almost always favors Samuel Beckett's tense and symbolic style of writing. His ability to convince us that he is portraying life-like circumstances in conventionally realistic terms is a significant element of his success.